The linguistics of Textual Genres at the Service of the Teaching of French as a Foreign Language - Qahraman Sulaiman Ahmed (Zanco Journal of Humanity Sciences)
The educational texts did not take the place they deserve in the field of teaching and learning foreign languages ​​despite their effective role in theoretical and applied research in this field. So the main objective of our study was based on highlighting the types of discourse and its role in the research of teaching and learning French language, more clearly this study focused on two main strategies. The first is an explanation of linguistic concepts and their role in the process of teaching and learning the French language, such as text, type and discourse, seeking to clarify the foundations of linguistic analysis and its components in the language. While the second axis deals with the application of these concepts in the context of teaching and learning French as a foreign language.